Assessment of oxidative stress in babies under phototherapy for neonatal jaundice - Anitha Nancy Thiagarajan; Parkash Chand; Ballambattu Vishnu Bhat; Magadi Gopalakrishna Sridhar (International Journal of Advanced Medical and Health Research, 2014)
Background: Neonatal jaundice is a common condition that can be treated with phototherapy. Phototherapy may cause oxidative stress in addition to the usual side effects. Aim: In this study, the oxidative stress in babies with neonatal jaundice was assessed before and after phototherapy by estimating plasma malondialdehyde (MDA) level. Methods: Eighty babies with neonatal jaundice were chosen for the study. Among them, 40 babies whose total serum bilirubin level was >15 mg/dl formed the case group and the other 40 babies with total serum bilirubin level <15 mg/dl who did not require phototherapy formed the control group. Total serum bilirubin was measured using Automated Clinical Chemical Analyser with standard reagent kit. Plasma MDA was estimated by Satoh′s method using spectrophotometry. Results: The plasma MDA level, which is one of the oxidant markers, was significantly elevated in post-phototherapy cases compared to pre-phototherapy and controls. Conclusion: Phototherapy results in significant oxidative stress among babies with neonatal hyperbilirubinemia. So, usage of phototherapy should be restricted to those with significant hyperbilirubinemia.